Pengaruh Kepribadian, Motivasi Kerja, dan Keterampilan Kerja Terhadap Kinerja Anggota Keluarga Besar Waria yang Memiliki UMKM di Yogyakarta - Sunyoto, Danang; Mulyono, Agus (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Aim – This research aims to develop and test the influence of personality, motivation and work skills on performance. The population of this study are all members of the NGO KEBAYA (Big Family of Waria Yogyakarta) which has a private business of 60 people. Design / Methodology / Approach – Population or saturated sample research, data collection methods using questionnaires and observation. Descriptive and quantitative qualitative data analysis methods. Research Results–Personality, work motivation and work skills play a positive and significant role in the performance of KEBAYA NGO members. Originality – Personality development, work motivation and skills in the research object are special (transvestites).